Strategi Kebijakan Peningkatan Peran Pengabdian Masyarakat STAIN Majene dalam Pemberdayaan Ekonomi Masyarakat - Pakhri (JURNAL ILMIAH GEMA PERENCANA, 2025)
This policy paper discusses strategies for enhancing the role of community service at STAIN Majene in local economic empowerment in Majene Regency, West Sulawesi. The background of this study is the low effectiveness of community service caused by the lack of strategic collaboration between STAIN Majene and local economic stakeholders, the absence of specific institutional structures, and the lack of formal operational procedures. This study uses a qualitative method with an evidence-based policy approach to descriptive analysis. Data were collected through literature studies, official document analysis, field observations, and informal interviews with business actors and community leaders. Primary and secondary data were then analyzed using the public policy evaluation framework according to William N. Dunn, which includes six criteria: effectiveness, efficiency, adequacy, equity, responsiveness, and precision. The analysis results show that the establishment of a special external partnership unit under P3M is the most strategic policy alternative, with the potential to drive institutional transformation and strengthen cross-sector collaboration in economic empowerment programs. This policy paper recommends the establishment of such a unit with support from internal regulations, functional organizational structure, digital information systems, and integration into the campus strategic plan. These findings contribute theoretically to the development of a collaborative service model based on Islamic values and local needs, and practically offer an adaptive and inclusive institutional model for PTKIN in underdeveloped regions. With this strategy, STAIN Majene has the opportunity to become a pioneer in transformative, impactful, and sustainable community service practices.